2021
DOI: 10.1021/acsinfecdis.1c00414
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum Acetyl-CoA Synthetase Is Essential for Parasite Intraerythrocytic Development and Chromatin Modification

Abstract: The malaria parasite Plasmodium falciparum possesses a unique Acetyl-CoA Synthetase (PfACS), which provides acetyl moieties for different metabolic and regulatory cellular pathways. We characterized PfACS and studied its role focusing on epigenetic modifications using the var gene family as reporter genes. For this, mutant lines to modulate plasmodial ACS expression by degron-mediated protein degradation and ribozyme-induced transcript decay were created. Additionally, an inhibitor of the human Acetyl-CoA Synt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…To test this, we used a modified TetR-DOZI system 52 plasmid pKD 53 to knock down ACS expression in Δlipl2 parasites, generating the ↓acs/Δlipl2 parasite line. Successful insertion of the pKD plasmid (Figure 7-figure supplement 2) resulted in tagging of ACS with 3xHA tag allowing us to localize the ACS protein to the parasite nucleus (Figure 7C) as has been recently reported [31][32][33] .…”
Section: Acetate Bypass Of Mitochondrial Metabolism Relies On Nuclear...mentioning
confidence: 60%
See 2 more Smart Citations
“…To test this, we used a modified TetR-DOZI system 52 plasmid pKD 53 to knock down ACS expression in Δlipl2 parasites, generating the ↓acs/Δlipl2 parasite line. Successful insertion of the pKD plasmid (Figure 7-figure supplement 2) resulted in tagging of ACS with 3xHA tag allowing us to localize the ACS protein to the parasite nucleus (Figure 7C) as has been recently reported [31][32][33] .…”
Section: Acetate Bypass Of Mitochondrial Metabolism Relies On Nuclear...mentioning
confidence: 60%
“…In P. falciparum parasites, labeled acetate is incorporated into acetyl-CoA, and the enzyme Acetyl-CoA Synthetase (ACS) has been hypothesized to catalyze this reaction 29,32 . We explored this activity using Δlipl2 and parental parasites labeled with 13 C-acetate, 13 C-glucose or 13 C-glutamine.…”
Section: Acetate Bypass Of Mitochondrial Metabolism Relies On Nuclear...mentioning
confidence: 99%
See 1 more Smart Citation
“…Elucidating whether the histone PTMs that characterize differentiation initiation in other eukaryotes, such as H3K4 H3K9, H3K20 methylation (Bhanu et al, 2016) and global histone acetylation (Meshorer et al, 2006;Tan et al, 2013), is also associated with sexual commitment in P. falciparum remains an interesting question. The impact of the metabolic shift between asexual and gametocytes on the chromatin milieu also warrants clarification, with the indication that loss of function of acetyl-CoA synthetase leads to chromatin hypoacetylation and that the restriction of S-adenosyl-L-methionine availability can cause heterochromatin formation (Prata et al, 2021;Summers et al, 2021).…”
Section: Histone Ptms That Orchestrate the Asexual To Sexual Stage Tr...mentioning
confidence: 99%
“…ACS Infectious Diseases is contributing to this joint virtual special issue focused on epigenetics with 11 publications in the form of nine innovative research articles, one Perspective, and one Viewpoint. Not surprisingly, histone deacetylase (HDAC) is the target class with a major presence (four research articles), as HDAC has already shown its therapeutic potential to treat infectious diseases. Also notable is the increase of interest in bromo­domains in protozoa; their potential as novel targets against protozoans-mediated diseases is discussed in a Viewpoint and two articles. , Finally, the characterization of acetyl-CoA synthetase as an interesting target for the development of antiplasmodial drugs, the profiling of epigenetic modulators against hemo­protozoan parasites, and two publications focused on the role of the host , complete the contributions from ACS Infectious Diseases to this virtual special issue. We thank Drs.…”
Section: Acs Infectious Diseasesmentioning
confidence: 99%